Implementasi Timing - Sync Untuk Sensor Networks Pada Jaringan Sensor Multihop - Budiman Eka Atmaja Timur; Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Development of Wireless Sensor Network (WSN) has been growing rapidly, especially for human life. WSN applications are generally used for the needs of monitoring, tracking and controling. In some applications, WSN uses many sensors are deployed randomly in a particular area in order to obtain extensive information. However, WSN still have some issues that need to be solved, such as interference in data transmission if there are many WSN nodes send data at the same time and using the same frequency channel, the data collision will occur. One of many solutions to solve this issue is Time Division Multiple Acces (TDMA) method. Time division multiple access (TDMA) is a channel access method for shared medium networks. It allows several users to share the same frequency channel by dividing the signal into different time slots. TDMA made those WSN nodes to send their own data sequentiallly, so the nodes will send the data at a different time according to the slot time they have got before. In order to apply the TDMA method, the local clock of the entire WSN nodes must be synchronize, but there are significant issues in wireless synchronization, because the propagation delay is too long, event the small area. The aim of this research is to apply one of the best time synchronization algorithm called Time-sync Protocol in Sensor Network (TPSN) to support the TDMA method. After implemented, there are some problems that occur as the node can not pass TDMA to another node, unreliable, work only few nodes, and small scale. Due to this issue, the developer wants to add some features what can cover up this weakness using library rf24 arduino. The system was tested, and The results showed good result with more flexible for multiple network. The results show the ability to send messages by going through other nodes with a predetermined schedule.